(untitled) (Journal of the College of Basic Education, 2024)
The effective Regulation and Ethical of Artificial Intelligence is an urgent policy concern. Legislatures and regulators do not possess the specialized technical expertise necessary to effectively convert popular requests into legislative mandates. The excessive dependence on industry self-regulation results in a lack of accountability for AI ethical system and users in meeting democratic requirements. The concept of Ethical Frameworks involves governments mandating the entities subject to regulation to get regulatory assistance from a private regulator. This AI Ethical Frameworks has the potential to address the shortcomings of both command-and-control regulation and self-regulation. Most of advanced states provide governments the opportunity to set policy priorities for AI Ethical Frameworks, while using market forces and industry research and development (R&D) to develop the most effective ways of regulation to set up Ethical Frameworks that align with policymakers’ goals.